Population Dynamics of Bifidobacterium Species in Human Feces during Raffinose Administration Monitored by Fluorescence In Situ Hybridization-Flow Cytometry - Dinoto, Achmad; Marques, Tatiana M; Sakamoto, Kanta; Fukiya, Satoru; Watanabe, Jun; Ito, Susumu; Yokota, Atsushi (Applied and Environmental Microbiology, 2006)
The population dynamics of bifidobacteria in human feces during raffinose administration were investigated at the species level by using fluorescence in situ hybridization (FISH) coupled with flow cytometry (FCM) analysis. Although double-staining FISH-FCM using both fluorescein isothiocyanate (FITC) and indodicarbocyanine (Cy5) as labeling dyes for fecal samples has been reported, the analysis was interfered with by strong autofluorescence at the FITC fluorescence region because of the presence of autofluorescence particles/debris in the fecal samples. We circumvented this problem by using only Cy5 fluorescent dye in the FISH-FCM analysis. Thirteen subjects received 2 g of raffinose twice a day for 4 weeks. Fecal samples were collected, and the bifidobacterial populations were monitored using the established FISH-FCM method. The results showed an increase in bifidobacteria from about 12.5% of total bacteria in the prefeeding period to about 28.7 and 37.2% after the 2-week and 4-week feeding periods, respectively. Bifidobacterium adolescentis, the Bifidobacterium catenulatum group, and Bifidobacterium longum were the major species, in that order, at the prefeeding period, and these bacteria were found to increase nearly in parallel during the raffinose administration. During the feeding periods, indigenous bifidobacterial populations became more diverse, such that minor species in human adults, such as Bifidobacterium breve, Bifidobacterium bifidum, Bifidobacterium dentium, and Bifidobacterium angulatum, proliferated. Four weeks after raffinose administration was stopped, the proportion of each major bifidobacterial species, as well as that of total bifidobacteria, returned to approximately the original values for the prefeeding period, whereas that of each minor species appeared to differ considerably from its original value. To the best of our knowledge, these results provide the first clear demonstration of the population dynamics of indigenous bifidobacteria at the species level in response to raffinose administration.